2015
DOI: 10.1002/mop.29585
|View full text |Cite
|
Sign up to set email alerts
|

Research on the propagation constant of the periodically slotted rectangular waveguide by equivalent circuit method

Abstract: The influence of the structural parameters on the propagation constant of the leaky rectangular waveguide is studied by an equivalent circuit method and the dispersion equations are derived by the theory of transmission line. Using these equations, variation of propagation constant with the structural parameters is obtained and analyzed. And the propagation constants obtained from the equivalent circuit method were compared with those from the full‐wave simulation results. Both the results show that there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…In this paper, a novel periodic leaky-wave antenna based on the rectangular waveguide is designed for broadside radiation, as shown in Figure 2(a). It is found that, for periodically slotted rectangular waveguide, the slot itself can be equivalent to the inductance L s and the capacitance C s [6], which are connected in parallel, as shown in Figure 1(c). However, L s is a series inductance and C s is too small to reach balance.…”
Section: Structure and Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, a novel periodic leaky-wave antenna based on the rectangular waveguide is designed for broadside radiation, as shown in Figure 2(a). It is found that, for periodically slotted rectangular waveguide, the slot itself can be equivalent to the inductance L s and the capacitance C s [6], which are connected in parallel, as shown in Figure 1(c). However, L s is a series inductance and C s is too small to reach balance.…”
Section: Structure and Mechanismmentioning
confidence: 99%
“…However, L s is a series inductance and C s is too small to reach balance. In order to introduce the left-handed transmission line property, the interdigital slots are cut on the upper surface to produce enough series capacitance C L [6], and metal vias are set between upper and lower walls to produce enough shunt inductance L L [10]. e transverse interdigital slots and metal vias are periodically set along the waveguide.…”
Section: Structure and Mechanismmentioning
confidence: 99%
See 1 more Smart Citation